Jak rozumět "pohanským reliktům": folklór baltských zemí jako zdroj pro studium předkřesťanských tradic starých Baltů = How to deal with "pagan relics" : Baltic folklore as a source for the study of the pre-Christian traditions of the Balts - Reichstäter, Jan (Religio, 2015)
Due to the peripheral geographic location of the Baltic region within the European continent, as well as to its late Christianization, the folklore of the Baltic countries preserved many pre-Christian archaisms. For this reason, folkloric sources have frequently been used in the study of Baltic paganism (and even for the reconstruction of Indo-European beliefs) since the beginning of scientific research in this field. In virtually all constitutive elements of folk-lore involving a religious dimension (narrative genres, traditional calendar and feasts, folk art) continuities with pre-Christian cultures can be observed. These "archaic elements", preserved especially in rural traditions, represent, however, rather "marginal" or "secondary" heritage of the old faith, since the main constitutive features of the pagan religion (i.e. the structure of the pantheon, the main corpus of the mythology, idols and images of gods, related cults and rituals, institutions of priesthood) were nearly completely removed during the long process of the Christianization of the indigenous people between the 13th and 17th centuries. The main problem for the study of pagan relics in Baltic folklore lies in the absence of knowledge of their micro-histories. Another important problem is connected with the quality and quantity of folkloric sources from national archives, especially those collected before World War I. Although qualitative methods developed considerably during the 20th century, ironically the same century also witnessed the rapid demise of folklore traditions, nowadays maintained and protected rather as a foundation for the national identities of Lithuanians and Latvians.